Alpinia oxyphylla Miq. and Its Active Compound P-Coumaric Acid Promote Brain-Derived Neurotrophic Factor Signaling for Inducing Hippocampal Neurogenesis and Improving Post-cerebral Ischemic Spatial Cognitive Functions - He, Yacong; Chen, Shuang; Tsoi, Bun; Qi, Shuhua; Gu, Bing; Wang, Zhenxing; Peng, Cheng; Shen, Jiangang (Frontiers in Cell and Developmental Biology, 2021)
Alpinia oxyphylla Miq. (AOM) is a medicinal herb for improving cognitive functions in traditional Chinese medicine for poststroke treatment, but its efficacies and underlying mechanisms remain unknown. In the present study, we tested the hypothesis that AOM could induce adult hippocampal neurogenesis and improve poststroke cognitive impairment via inducing brain-derived neurotrophic factor (BDNF) signaling pathway. In order to test the hypothesis, we performed both in vivo rat experiments using transient middle cerebral artery occlusion (MCAO) model and in vitro neural stem cell (NSC) experiments using oxygen–glucose deprivation plus reoxygenation. First, AOM treatment significantly up-regulated the expression of BDNF, tropomycin receptor kinase B (TrkB), and phosphorylated AKT (p-AKT) in the hippocampus, enhanced adult hippocampal neurogenesis, and improved the spatial learning/memory and cognitive functions in the post-MCAO ischemic rats in vivo. Next, in vitro studies confirmed p-coumaric acid (P-CA) to be the most effective compound identified from AOM extract with the properties of activating BDNF/TrkB/AKT signaling pathway and promoting NSC proliferation. Cotreatment of BDNF/TrkB-specific inhibitor ANA12 abolished the effects of P-CA on inducing BDNF/TrkB/AKT activation and the NSC proliferation. Finally, animal experiments showed that P-CA treatment enhanced the neuronal proliferation and differentiation in the hippocampus, improved spatial learning and memory functions, and reduced anxiety in the transient MCAO ischemic rats. In conclusion, P-CA is a representative compound from AOM for its bioactivities of activating BDNF/TrkB/AKT signaling pathway, promoting hippocampal neurogenesis, improving cognitive functions, and reducing anxiety in post–ischemic stroke rats.